Maintaining nocturnal glycemic status using insulin glargine - Dr. Deepak Verma; Dr. Nikhil Patil; Dr. Nitasha Soni; Dr. Pravin Pant; Dr. S K Mehlotra (Medico Research Chronicles)
Hypoglycemia is a major limiting factor in achieving glycemic control in patients with diabetes. The American Diabetes Association recommends an HgA1C goal of less than 7% in most patients, and the American Association of Clinical Endocrinologists recommends an HgA1C less than 6.5%, if achievable without significant hypoglycemia. Landmark studies, such as the Diabetes Control and Complications Trial (DCCT) and the United Kingdom Prospective Diabetes Trial have clearly shown that tight glycemic control can prevent or delay the development of microvascular complications, such as retinopathy, nephropathy, and neuropathy, in type 1 and type 2 diabetes, but with aggressive glycemic targets comes an increase of hypoglycemia risk.